TINDAK TUTUR ASERTIF DALAM BASA-BASI BANJAR - Rissari Yayuk (Multilingual, 2014)
Conventional politeness understood as a form of communication between players that contain the word civility, hospitality, social ethics, and tolerance. The present study investigates the problem assertive speech act in manners that are found in the social life of the community Banjarese. The aim is to achieve assertive speech describing the type of reaction. The method used is descriptive. The results showed that assertive speech acts in Banjarese blunt language consists of assertive speechacts expressing something, speculating, complaining , acknowledging, and reporting.